Primal-dual links to spatial equilibrium market model for palm oil in Nigeria (2016)
"Distribution of agricultural produce is undertaken to bridge the gap between production and consumption arising due to spatial separation between areas of surplus and deficit. An investigation of primal-dual links to spatial equilibrium model and integration of palm oil markets in Nigeria was carried out using transportation model. Two-stage sampling technique was used to collect data from 3 markets and 276 distributors. Data were analyzed using linear programing model. Average cost of transportation per mode was bus (N17, 173), truck (N 10,357) and lorry (N5,831 ) respectively. Total transportation cost of N347,809,600.6k was observed compared to a minimized objective cost of NI42,536,800.30k produced by the program. Highest optimal allocation to the destination markets using the different mode of transportation were Port Harcourt-Lagos by lorry (103,200 MT), Owerri- Maiduguri by truck (21,200 MT) and Ondo-Lagos by bus (19,800 MT) respectively. Subsidized cost of public transport facilities will reduce high cost of transportation. "